2020
DOI: 10.1002/mnfr.202000291
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Intake of Pork Meat Proteins Altered the Composition of Gut Microbiota and Host‐Derived Proteins in the Gut Contents of Mice

Abstract: Scope This study is to investigate the effects of long‐term intake of pork protein on the composition of gut microbiota and proteins in mice. Methods and results C57BL/6J mice are fed pork meat protein diets for 240 days, and the composition of gut microbiota and proteins in luminal contents from the duodenum to the colon are analyzed by 16S rRNA gene sequencing and LC‐MS/MS. The stewed pork protein diet group has a highly similar microbiota composition to that of the cooked pork protein diet group, but differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The Methanobrevibacter genus, which contained the most abundant methanogenic archaea in animals, increased energy absorption efficiency by cooperating with hydrogen-producing Hydrogenoanaero microorganisms highly enriched in the obese human gut [ 70 ]. Defluviitaleaceae UCG-011 was reported to play a major part in response to alterations in intestinal luminal proteins [ 71 ]. At the same time, Oscillibacter was involved in the utilization of carbohydrates and proved to increase rumen fermentation in calves [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Methanobrevibacter genus, which contained the most abundant methanogenic archaea in animals, increased energy absorption efficiency by cooperating with hydrogen-producing Hydrogenoanaero microorganisms highly enriched in the obese human gut [ 70 ]. Defluviitaleaceae UCG-011 was reported to play a major part in response to alterations in intestinal luminal proteins [ 71 ]. At the same time, Oscillibacter was involved in the utilization of carbohydrates and proved to increase rumen fermentation in calves [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased proportion of inflammation-related bacterium ( Oscillospiraceae ) and Erysipelotrichaceae_UCG-003 were linked to the sub-health status in the host [ 62 , 81 ]. Xie et al [ 71 ] documented that Lachnoclostridium had a crucial role in response to variations in intestinal proteins, while Eisenbergiella was reported to be connected with weight gain in humans [ 66 ]. These data conveyed the message that the colonization of the gut microbiome is a constantly changing and non-fixed ecosystem influenced by the factors such as stocking density and age.…”
Section: Discussionmentioning
confidence: 99%
“…Total peptide signals within each run were normalized before quantitation. Afterwards, the counts of peptides between samples were compared to obtain a matrix of protein ratios, calculated as the median of all ratios for peptides 44 . Protein abundance was calculated on the basis of the normalized spectral protein intensity (LFQ intensity).…”
Section: Methodsmentioning
confidence: 99%
“…Protein abundance was calculated on the basis of the normalized spectral protein intensity (LFQ intensity). OmicsBean ( www.omicsbean.cn ) was used to analyze the selected proteome data, in which GO analysis and KEGG pathway analysis were conducted 44 .…”
Section: Methodsmentioning
confidence: 99%
“…[109,110] In a study investigating long-term dietary intervention, consumption of different processed pork products at the recommended dosage changed the composition of the gut microbiota, but did not cause serious inflammation. [111] However, consuming some pork products could cause problems for immune deficient individuals with impaired innate immune systems. The study indicated that administration of processed meat proteins had limited influence on the physiology and gut health of wild-type mice, but a significant negative impact on Rag1-/-mice (adaptive immune-deficient mice).…”
Section: Protein and Gut Microbiotamentioning
confidence: 99%